Reproductive Health Service Utilization and Associated Factors: The Case of North Shewa zone Youth, Amhara Region, Ethiopia - Negash, Wassie; Dessalegn, Muluken; Yitayew, Berhanu; Demsie, Mohammed; Wagnew, Maereg; Nyagero, Josephat (Pan African Medical Journal)
Introduction Many youth are less informed, less experienced and less comfortable in utilizing reproductive health services. In the Sub-Saharan region the adolescents account for a higher proportion of new HIV infections and unmet need for reproductive health (RH) services. This study assessed reproductive health service utilization and associated factors among the youth in Amhara Region, Ethiopia. Methods A community based cross-sectional study was conducted from June 15-July 30, 2014. Three hundred ninety one youth were selected by systematic random sampling technique and interviewed using structured questionnaire. Data were anlyzed using SPSS windows version 20. Multiple logistic regression was done to control potential confounding variables. P-values <0.05 were considered statistically significant. Results Three hundred and nighty one in-school and out-of-school youth were interviewed; 256 (65.5%) participants were in school and 209 (53.5%) were males. Almost all respondents (93.9%) had heard about reproductive health services and a third 129 (33%) had ever practiced sexual intercourse and 54.7% of them had utilized at least one reproductive health services. Never had sexual intercourse (AOR=3.693, 95%CI: 1.266, 10.775), families that asked their children about friends (parental monitoring) (AOR=1.892, 95%CI: 1.026, 3.491), know where service provided (AOR=3.273, 95%CI: 1.158, 9.247), youths who reads newspaper readers (AOR=3.787, 95%CI: 1.849were independent predictors of youth reproductive service utilization at 95 % CI and p-value <0.05%. Conclusion Even though the youth have information about reproductive health services, youth reproductive health services utilization is very low. Therefore, building life skill, facilitating parent to child communication, establishing and strengthening of youth centres and increasing awareness for youth about those services are important steps to improve adolescents' reproductive health (RH) service utilization.
© Wassie Negash et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Youth; Reproductive health service; Utilization cross sectional; Regression